(untitled) (Jurnal Adabiya, 2020)
This research aims to describe Form and reason of use of Tamiang Malay Language swears word by Aceh Tamiang Comunity Akademy. Swear words are often used to pout other people or express resentment so that it feels far from national ethics and culture. the researcher used sociolinguistic studies to approach the phenomenon. The researcher attempts to associate the choice of variety and variations of swear words to find the form and the reasons of use swear word at the student level. This research method uses descriptive qualitative research methods, this means, the researcher attempted to present data on the use of swear words to students using in-depth interviews and Focus Group Discussion.This study concludes that there are differences in form and reason of use of Tamiang Malay Language swear word by Aceh Tamiang Comunity Akademy.This research aims to describe Form and reason of use of Tamiang Malay Language swears word by Aceh Tamiang Comunity Akademy. Swear words are often used to pout other people or express resentment so that it feels far from national ethics and culture. the researcher used sociolinguistic studies to approach the phenomenon. The researcher attempts to associate the choice of variety and variations of swear words to find the form and the reasons of use swear word at the student level. This research method uses descriptive qualitative research methods, this means, the researcher attempted to present data on the use of swear words to students using in-depth interviews and Focus Group Discussion.This study concludes that there are differences in form and reason of use of Tamiang Malay Language swear word by Aceh Tamiang Comunity Akademy.